Water treatment method using activated carbon

By using activated carbon of specific composition, its average particle size, specific surface area and porosity have a specific range. Combined with the water treatment method, the problem of low removal efficiency of fluorine-containing organic compounds in the prior art is solved, and the effect of efficient removal and environmental risk reduction is achieved.

CN119750703APending Publication Date: 2025-04-04KURARAY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510143972.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-09-23
Filing Date
2021-09-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art has low treatment efficiency when removing fluorine-containing organic compounds (PFCs), making it difficult to meet the need to reduce environmental risks.

Method used

Activated carbon with an average particle size of 0.1 to 10 mm, a BET specific surface area of ​​500 m2/g or more and 2000 m2/g or less, and an internal porosity of 10% or more and 40% or less was used to contact water containing fluorine-containing organic compounds, and the fluorine-containing organic compounds were removed by efficient adsorption of activated carbon.

Benefits of technology

The efficient removal of fluorine-containing organic compounds is achieved, and the content of fluorine-containing organic compounds in the treated water can be reduced to below 0.1 ppb, significantly reducing environmental risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750703A_ABST
    Figure CN119750703A_ABST
Patent Text Reader

Abstract

The invention relates to a water treatment method using activated carbon. The purpose of the present invention is to provide an activated carbon capable of efficiently removing a fluorine-containing organic compound, and a method for treating water containing a fluorine-containing organic compound. One aspect of the present invention relates to an activated carbon having an average particle diameter of 0.1-10 mm, a BET specific surface area of 500-2000 m2 / g (inclusive), and a porosity of 10-40% (inclusive) in the particle as determined by X-ray CT. Another aspect of the present invention relates to a water treatment method having a step for obtaining treated water having a fluorine-containing organic compound content of 0.1 ppb or less by bringing the activated carbon according to any one of claims 1-3 into contact with water to be treated containing a fluorine-containing organic compound.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention application is a divisional application of PCT patent application PCT / JP2021 / 033257, with the application date of September 10, 2021, and the invention name of the invention patent application "Activated carbon and water treatment method using the same". The application number of the parent case entering China is 202180063878.8. Technical Field

[0002] The present invention relates to a water treatment method using activated carbon. Background Art

[0003] Fluorinated organic compounds have special properties that cannot be achieved by other substances (excellent heat resistance and chemical resistance, usability even under harsh conditions, no light absorption, etc.), so they have been used in various applications such as surfactants, emulsifiers, water repellents, fire extinguishers, waxes, carpet cleaners, coating agents, etc. Recently, their use as functional materials such as semiconductor surface treatment agents and fuel cell components has also increased.

[0004] However, a few years ago, researchers in the United States and Canada began to report that some fluorinated organic compounds can accumulate in environmental water and wildlife. Perfluorooctanoic acid (PFOA: C7F 15 Perfluorooctane sulfonic acid (PFOS: C8F 17 SO3H) as the representative of perfluorosulfonic acid, and then researchers in Europe and Japan also joined the environmental analysis research, and the results made it clear that these compounds exist in the environment around the world, including Japan. Based on this situation, measures have been taken to reduce the environmental risks of fluorinated organic compounds (PFCs).

[0005] Patent Document 1 discloses a method for recovering PFOA using granular activated carbon.

[0006] The method of using activated carbon in the treatment of PFOA and the like, such as Patent Document 1, has obvious advantages in terms of economic efficiency, but the treatment efficiency of the prior art is not satisfactory. In view of the above situation, the object of the present invention is to provide an activated carbon capable of efficiently removing fluorinated organic compounds, and a method for treating water containing fluorinated organic compounds.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: U.S. Patent Publication No. 2005 / 0000904 Summary of the invention

[0010] The present inventors have conducted intensive studies and have found that fluorinated organic compounds can be efficiently removed by using a fluorinated organic compound removing material or a water treatment method having the following constitution.

[0011] One aspect of the present invention relates to an activated carbon having an average particle size of 0.1 to 10 mm and a BET specific surface area of ​​500 m 2 / g and above and 2000m 2 / g or less, and the porosity inside the particles determined by X-ray CT is 10% or more and 40% or less.

[0012] In another aspect, the present invention relates to a water treatment method comprising the step of bringing the activated carbon into contact with water to be treated containing fluorinated organic compounds to obtain treated water having a fluorinated organic compound content of 0.1 ppb or less. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is an X-ray CT cross-sectional image of the activated carbon of Example 1.

[0014] Figure 2 This is an image processing screen of the X-ray CT cross-sectional image of the activated carbon of Example 1.

[0015] Figure 3 This is an X-ray CT cross-sectional image of the activated carbon of Comparative Example 1.

[0016] Figure 4 This is an image processing screen of an X-ray CT cross-sectional image of the activated carbon of Comparative Example 1. DETAILED DESCRIPTION

[0017] Embodiments of the present invention will be described in detail below, but the present invention is not limited to these descriptions.

[0018] The activated carbon according to one embodiment of the present invention has an average particle size of 0.1 to 10 mm and a BET specific surface area of ​​500 m 2 / g and above and 2000m 2 / g or less, and an activated carbon having a porosity inside the particles of 10% or more and 40% or less as determined by X-ray CT.

[0019] According to the activated carbon of the present invention, fluorine-containing organic compounds in water to be treated can be adsorbed extremely efficiently.

[0020] The average particle size of the activated carbon of the present embodiment is 0.1 mm or more, preferably 0.5 mm or more, and more preferably 1.0 mm or more. In addition, the average particle size of the activated carbon of the present embodiment is 10 mm or less, preferably 8 mm or less, and more preferably 7 mm or less. When the average particle size is above the above lower limit, the pore volume can be fully ensured, so it is preferred. It should be noted that in this specification, the average particle size of the activated carbon refers to the average particle diameter measured according to JIS K1474.

[0021] The specific surface area (BET specific surface area) of the activated carbon of this embodiment is 500 m 2 / g and above and 2000m 2 / g or less, and the specific surface area is calculated by the BET method (multi-point method) from the nitrogen adsorption isotherm obtained from the nitrogen adsorption at 77K. The BET specific surface area is preferably 550m 2 / g or more, more preferably 600m 2 / g or more. In addition, the BET specific surface area is preferably 1900m 2 / g or less, more preferably 1700m 2 When it is within the above range, the activated carbon of the present embodiment has excellent removal capability (adsorption capability) of fluorinated organic compounds and excellent mechanical strength.

[0022] The activated carbon of this embodiment has pores inside. By making the activated carbon have appropriate pores inside, when the activated carbon is used as a fluorinated organic compound removal material, the fluorinated organic compounds in the treatment target water can be efficiently removed. As shown in the following examples, the activated carbon of this embodiment can be observed by X-ray CT without being destroyed, and the fine pores can be measured without damaging it.

[0023] The porosity of the activated carbon of the present embodiment, obtained by X-ray CT, inside the particles is 10% or more and 40% or less. The porosity is preferably 12% or more, more preferably 15% or more, and further preferably 20% or more. In addition, the porosity is preferably 38% or less, more preferably 35% or less. When the porosity is above the lower limit, the inside of the activated carbon can be suitably used for the adsorption of fluorine-containing organic compounds. In addition, when the porosity is below the upper limit, the mechanical strength is high and the shape can be maintained.

[0024] Here, the porosity inside the particles obtained by X-ray CT is obtained as described below. First, a plurality of (more than 1,000) continuous cross-section images of the target activated carbon are taken using X-ray CT (for example, using Xradia520Versa manufactured by Carl Zeiss). Secondly, from the images obtained by the shooting, more than 40 images existing between the first section taken and the last section taken are extracted at equal intervals, and the portion corresponding to the pores of each extracted section is extracted by image processing, and the pore area per unit area of ​​the section is obtained. Finally, for the ratio of the pore area per unit area of ​​each section, the average value of the extracted 40 or more images is obtained, and the average value is used as the porosity inside the activated carbon particles obtained by X-ray CT. It should be noted that in this specification, the detection of about 1 μm 2 The above ones are regarded as pores.

[0025] The activated carbon of this embodiment preferably has an iodine adsorption amount of 900 mg / g or more. In addition, the iodine adsorption amount is preferably 1200 mg / g or less. The iodine adsorption amount becomes an indicator of the volume of pores with a diameter less than 1 μm. When the iodine adsorption amount is within the above range, the strength can be maintained and the adsorption amount of the fluorine-containing organic compound can be more sufficient.

[0026] As the raw material of the activated carbon of the present embodiment, for example, plant-based carbonaceous materials (such as wood, wood shavings, charcoal, fruit shells such as coconut shells or walnut shells, fruit seeds, pulp manufacturing byproducts, lignin, waste molasses and other plant-based materials), mineral-based carbonaceous materials (such as peat, lignite, brown charcoal, bituminous coal, anthracite, coke, coal tar, coal tar and other coal-based materials; mineral-based materials such as petroleum distillation residues, petroleum asphalt and other petroleum-based materials), synthetic resin-based carbonaceous materials (such as phenolic resins, polyvinylidene chloride, acrylic resins and other synthetic resin-based materials), natural fiber-based carbonaceous materials (such as cellulose and other natural fibers, rayon and other regenerated fibers and other natural fiber-based materials) and the like can be cited. These carbonaceous materials can be used alone or in combination of two or more. It is known that organic fluorine compounds are adsorbed on activated carbon by hydrophobic interactions. From the perspective of the balance between high specific surface area and hydrophobicity, the mechanical strength when provided for heat treatment, etc., it is preferred to use mineral-based carbonaceous materials, and it is particularly preferred to use activated carbon derived from asphalt carbon.

[0027] The activated carbon of the present embodiment can be manufactured, for example, as follows: dry-mix the carbonaceous material having weak or higher adhesion and the carbonaceous material having slight adhesion among the above-mentioned carbonaceous materials, perform heat treatment, and then activate the mixture. Here, the carbonaceous material having weak or higher adhesion refers to a carbonaceous material having an adhesion index exceeding 1. Slight adhesion refers to a carbonaceous material having an adhesion index of 1 or less, and the adhesion index may be 0. It should be noted that the adhesion index is measured by placing a sample in a specified crucible and heating it under specified conditions according to the crucible expansion test method of JIS M 88016, and comparing the generated residue with the standard contour.

[0028] As carbonaceous materials with weak or higher cohesiveness, plants, fruit shells, minerals, etc. can be cited, preferably mineral carbonaceous materials, and among minerals, coal carbonaceous materials are preferred for the reasons mentioned above. As such carbonaceous materials, weak cohesive carbon with a cohesive index of more than 1 and less than 4 is preferably used. In the case of insufficient cohesiveness and poor moldability, strong cohesive carbon with a cohesive index of more than 4 and asphalt can also be used in a suitable ratio.

[0029] As a slightly adhesive carbonaceous material, a mineral carbonaceous material is preferred, and a coal carbonaceous material is preferred. In addition, the slightly adhesive carbonaceous material preferably contains at least any one of an alkali metal and an alkaline earth metal. As alkali metals, potassium, sodium, etc. can be cited. In addition, as alkaline earth metals, calcium, etc. can be cited. In the slightly adhesive carbonaceous material containing an alkali metal and / or an alkaline earth metal, the alkali metal and the alkaline earth metal are preferably more than 300ppm and less than 1100ppm in terms of the total amount of metal atoms. Among the alkali metal and the alkaline earth metal, calcium is particularly preferred. From the viewpoint of hardness and formability, it is more preferred to use a carbonaceous material having a calcium content of more than 300ppm and less than 1000ppm.

[0030] In the method for producing activated carbon of the present embodiment, when a raw material is used in which at least any one of alkali metals and alkaline earth metals is uniformly and highly dispersedly distributed in the structure of the carbonaceous material, localized pore formation is less likely to occur compared to a method in which a specific amount of a metal compound is added to the carbonaceous material and then activated, and uniform pore formation is performed, so that a suitable pore distribution can be obtained and the hardness is improved, which is preferred.

[0031] When manufacturing the activated carbon of the present embodiment, first, a carbonaceous material having weak or higher adhesion (hereinafter, sometimes referred to as material 1) and a carbonaceous material having slight adhesion (hereinafter, sometimes referred to as material 2, suitably containing alkali metals and / or alkaline earth metals) are dry mixed and pulverized. In addition to the above-mentioned carbonaceous material 1 and carbonaceous material 2, it is also permitted to add highly adhesive carbon or asphalt, etc., within the range that does not inhibit the effect of the present invention. The method for dry mixed pulverization is not particularly limited as long as the mixed pulverization can be performed in a manner that the ratio of the two carbonaceous materials is almost constant, and it can be easily implemented using a jaw crusher, a barrel crusher, a cone crusher, a single-roll crusher, a double-roll crusher, an impact crusher, a ball mill, a rod mill, or a high-speed mixer.

[0032] The mixing ratio of material 1 and material 2 can be determined according to the carbonaceous material used as the raw material and the target fluorine-containing organic compound removal ability and hardness. When the ratio of material 1 is too high, the hardness will increase, and on the other hand, it will inhibit the formation of pores with a pore diameter of more than 500nm, and there is a tendency for the removal ability of fluorine-containing organic compounds to decrease. In addition, when the ratio of material 1 is too low, there is a tendency for the moldability to decrease and the hardness to decrease. Therefore, it is preferred that material 1 and material 2 are mixed in a weight ratio of preferably 1:9 to 9:1, more preferably 2:8 to 6:4.

[0033] In the molding process, material 1 and material 2 are dry mixed and pulverized, and then temporarily molded by pressure molding. The pressure during pressure molding is preferably 140 kg / cm 2 More preferably 180kg / cm 2 In addition, the pressure during pressure molding is preferably 600 kg / cm 2 Below, more preferably 400kg / cm 2 Below, more preferably 360kg / cm 2 Below. When the pressure is above the above lower limit, material 1 and material 2 will not be restored to separate substances during the subsequent process of pulverization, but can be fully compounded, and pore formation can be appropriately performed. In addition, when the pressure is below the above upper limit, appropriate pores can be generated in the activated carbon production process. The device used for pressure molding is not particularly limited, and molding devices such as roller pressing, disc granulator, ring granulator, and extrusion can be used. In addition, the pressure and the shape of the molded product are not particularly limited, and can be determined as cylindrical, cylindrical, granular, spherical, sheet-like, etc. according to the purpose. The size of these is not particularly limited.

[0034] The obtained molded product can be crushed by a known crusher, such as a jaw crusher, a roller crusher, a ball mill, a rod mill or a high-speed mixer. The particle size of the crushed product is adjusted to a specified size such as 8 / 30 mesh. In practice, the particle size range of the activated carbon is preferably about 0.01 to 5.0 mm, more preferably about 0.05 to 3.0 mm, and the average particle size is preferably about 0.3 to 3.0 mm, more preferably about 0.5 to 1.0 mm. The crushed product (particles) after adjusting the particle size can be used for heat treatment. The heat treatment can be heated to 550 to 750°C in a reducing gas atmosphere. In order to obtain a carbide or activated carbon with higher performance and higher strength, it is preferably heat treated in two stages, for example, heating to 200 to 400°C at 5 to 30°C / min in an oxidizing gas atmosphere, and then heating to 550 to 750°C at 5 to 30°C / min in a reducing gas atmosphere.

[0035] The heat-treated (dry distilled) pulverized material can be further activated to become activated carbon. The activation can be carried out by: gas activation at 400 to 1000°C in an oxidizing gas atmosphere such as water vapor, carbon dioxide, air, propane combustion exhaust, LPG, or a mixed gas thereof; chemical activation at about 400 to 800°C in the presence of chemicals such as zinc chloride, phosphoric acid, calcium chloride, potassium sulfide, etc. Among them, it is preferred to use combustion gas activation at 900 to 1000°C under the circulation of combustion gas from the combustion of a mixed gas with a ratio of air to LPG in the range of about 1 to 0.03 to 1 to 0.06. The activation yield can be appropriately determined as needed based on the relationship between the removal capacity of fluorinated organic compounds and hardness.

[0036] After activation, the activated carbon obtained is washed with dilute hydrochloric acid or the like and adjusted to pH 5.0 to 7.0, thereby obtaining the activated carbon of the present embodiment. The pH of the activated carbon referred to here is the pH measured according to JIS K1474.

[0037] The activated carbon of this embodiment can be subjected to post-treatment such as surface chemical modification and physical loading of functional substances on the surface according to the application. Examples of such surface modification include adding salts, oxides, mineral acids of metals such as silver and iron, and treatments to make the surface acidic.

[0038] As the fluorine-containing organic compounds to be treated (adsorbed) by the activated carbon of the present embodiment, amphiphilic perfluoroalkane derivatives such as perfluoroalkane carboxylic acids, perfluoroalkyl sulfonic acids, 1H, 1H, 2H, 2H-perfluoroalkyl alcohols, etc. can be cited. As perfluoroalkane carboxylic acids, perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorononanoic acid, perfluorodecanoic acid, perfluoroundecanoic acid, perfluorododecanoic acid, etc. are included. As perfluoroalkyl sulfonic acids, perfluorobutane sulfonic acid, perfluorohexane sulfonic acid, perfluorooctane sulfonic acid, etc. are included. In particular, the activated carbon of the present embodiment has excellent adsorption capacity (removal capacity) for perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorooctane sulfonic acid, especially perfluorooctanoic acid.

[0039] The activated carbon of this embodiment can adsorb fluorinated organic compounds efficiently and for a long time, and therefore can be suitably used as a fluorinated organic compound removing material. Therefore, the present invention also includes a fluorinated organic compound removing material containing the above-mentioned activated carbon.

[0040] Another aspect of the present invention is a water treatment method, which has the following steps: the above-mentioned activated carbon is brought into contact with the treatment target water containing fluorinated organic compounds to obtain treated water with a fluorinated organic compound content of less than 0.1 ppb. Since the water treatment method of the present invention includes the above-mentioned structure, it is possible to obtain treated water with fluorinated organic compounds removed from the treatment target water containing fluorinated organic compounds with extremely high efficiency. Fluorinated organic compounds have special properties that cannot be achieved by other substances (excellent heat resistance and chemical resistance, can be used even under harsh conditions, no light absorption ability, etc.), and therefore have been used for various purposes. On the other hand, it is clear that some fluorinated organic compounds (for example, perfluorooctanoic acid (PFOA: C7F 15 Perfluorooctane sulfonic acid (PFOS: C8F 17 Perfluorosulfonic acids, such as SO3H), can accumulate in wild animals, and subsequent studies have shown that they exist in the environment worldwide. Based on this situation, reducing the content of fluorinated organic compounds in water to less than 0.1 ppb will help reduce environmental risks.

[0041] The inventors conducted in-depth research and found that when the concentration of fluorinated organic compounds in the water to be treated is low, when using conventional activated carbon, there is a limit to the reduction of fluorinated organic compounds even if a large amount of activated carbon is added. However, when using the specific activated carbon of this embodiment, extremely efficient treatment can be achieved.

[0042] Generally speaking, it is well known that the performance of activated carbon depends on its specific surface area. However, surprisingly, the efficiency of treating aqueous solutions with low concentrations of fluorinated organic compounds depends greatly on the internal properties of the activated carbon, and no clear correlation is observed with the specific surface area.

[0043] That is, in this embodiment, by using activated carbon whose intraparticle porosity measured by X-ray CT shows a certain constant value, fluorinated organic compounds can be efficiently removed, and treated water that contains almost no fluorinated organic compounds (fluorinated organic compound content is less than 0.1 ppb) can be obtained.

[0044] The fluorinated organic compound removing step in the present embodiment is a step of bringing treatment target water containing fluorinated organic compounds into contact with a fluorinated organic compound removing material containing specific activated carbon.

[0045] The concentration of the fluorinated organic compound in the water to be treated varies depending on the place where the water to be treated is collected and is not particularly limited, but is usually in the range of 0.1 to 1000 ppb.

[0046] The water treatment method of the present embodiment can efficiently remove fluorinated organic compounds even when the concentration of fluorinated organic compounds in the treatment target water is 1000 ppb or less, or further 100 ppb or less.

[0047] In the present specification, the concentration of the fluorine-containing organic compound can be measured using a liquid chromatography-tandem mass spectrometer (LC / MS / MS) manufactured by Waters Corporation under the following conditions. This measurement method is particularly useful for concentrations of 100 ppb or less.

[0048] HPLC system body: 2695 separation module

[0049] Mobile phase solvent: 45 vol% acetonitrile / 55 vol% 0.15% acetic acid aqueous solution

[0050] ·HPLC column: Atlantis dC183μm 2.1×30mm

[0051] Tandem quadrupole mass spectrometer: Quattro microAPI

[0052] The contact between the treatment object water and the activated carbon may be a batch contact in which activated carbon is added to the treatment object water, or a continuous contact in which the treatment object water flows through a column filled with activated carbon. In addition, the treatment may be carried out multiple times by batch contact, or multiple times by continuous contact, or a treatment combining batch contact and continuous contact may be carried out. It should be noted that the packed column in the continuous contact may be any of a moving bed type, a fixed bed type, or a fluidized bed type.

[0053] In batch contact, the contact time between the treatment target water and the activated carbon can be appropriately set according to the amount of activated carbon used, the concentration of fluorinated organic compounds in the treatment target water, etc., and is preferably 60 minutes or more from the viewpoint of ensuring a sufficient removal rate.

[0054] The amount of the activated carbon relative to the treatment target water is preferably 0.015 mass % or more, more preferably 0.05 mass % or more, and further preferably 0.10 mass % or more, relative to the treatment target water, from the viewpoint of ensuring sufficient treatment efficiency. In addition, from the viewpoint of volumetric efficiency, it is preferably 20 mass % or less, more preferably 10 mass % or less, and further preferably 5 mass % or less.

[0055] The water treatment method of the embodiment can obtain treated water having a fluorinated organic compound concentration of 0.1 ppb or less. The fluorinated organic compound concentration of the obtained treated water is more preferably 0.01 ppb or less, and further preferably 0.005 ppb or less.

[0056] In the water treatment method of this embodiment, when the treated water contains activated carbon, a step of removing the activated carbon may be further included. The method of removing the activated carbon is not particularly limited, and known methods such as filtration, sedimentation separation, centrifugal separation, and separation using a flocculant may be used.

[0057] Another aspect of the present invention is a water treatment device having the activated carbon of the present embodiment. In the water treatment device, the activated carbon may be contained in a treatment tank for treating the treatment object water, or may be provided with an activated carbon filling column for the treatment object water to flow. As long as the activated carbon is provided in a manner that the treatment object water and the activated carbon can be appropriately contacted, the manner is not limited. In addition, the manner in which the treatment object water and the activated carbon contact in the water treatment device may be batch-type or continuous. The filling column in the continuous contact may be any one of a moving bed type, a fixed bed type, and a fluidized bed type.

[0058] This specification discloses various aspects of technology as described above, and the main technologies thereof are summarized below.

[0059] That is, one aspect of the present invention relates to an activated carbon having an average particle size of 0.1 to 10 mm and a BET specific surface area of ​​500 m 2 / g and above and 2000m 2 / g or less, and the porosity inside the particles determined by X-ray CT is 10% or more and 40% or less.

[0060] According to this configuration, the activated carbon of the present invention can adsorb fluorine-containing organic compounds in the treatment target water with extremely high efficiency.

[0061] The iodine adsorption amount of the activated carbon is preferably 900 mg / g or more and 1200 mg / g or less. It is considered that this can maintain the strength of the activated carbon and make the adsorption amount of the fluorine-containing organic compound more sufficient.

[0062] In addition, the activated carbon is preferably made from coal, because it is considered that the activated carbon has better properties such as a balance between a high specific surface area and hydrophobicity and mechanical strength during heat treatment.

[0063] Another aspect of the present invention relates to a fluorine-containing organic compound removing material, which contains the above-mentioned activated carbon. In addition, another aspect of the present invention relates to a water treatment device, which includes the above-mentioned activated carbon.

[0064] In addition, another aspect of the present invention relates to a water treatment method, which comprises the following steps: contacting the above-mentioned activated carbon with water to be treated containing fluorinated organic compounds to obtain treated water having a fluorinated organic compound content of 0.1 ppb or less. According to the above-mentioned structure, treated water from which fluorinated organic compounds have been removed can be obtained with extremely high efficiency from water to be treated containing fluorinated organic compounds.

[0065] In the water treatment method, the fluorine-containing organic compound is preferably at least one selected from the group consisting of perfluorooctanoic acid, perfluorooctanoic acid salts, perfluorooctane sulfonic acid, and perfluorooctane sulfonate. It is considered that the effect of the present invention can be further exerted by this.

[0066] Example

[0067] Next, the present invention will be described based on Examples and Comparative Examples, but the present invention is not limited to the Examples.

[0068] (BET specific surface area)

[0069] The approximate formula derived from the BET formula is described below.

[0070]

[0071] Using the above approximate formula (I), the adsorption amount (v) at a predetermined partial pressure (p / p0) actually measured by the multi-point method based on nitrogen adsorption at liquid nitrogen temperature is substituted to obtain v: m The specific surface area (SSA: m 2 / g).

[0072]

[0073] In the above formula, vm is the adsorption amount required to form a monolayer on the sample surface (cm 3 / g), v is the actual measured adsorption amount (cm 3 / g), p0 is the saturated vapor pressure, p is the absolute pressure, c is a constant (reflecting the adsorption heat), and N is the Avogadro constant of 6.022×10 23 , a(nm 2 ) is the area occupied by the adsorbate molecules on the sample surface (cross-sectional area occupied by the molecules).

[0074] Specifically, the amount of nitrogen adsorbed on the carbon material at liquid nitrogen temperature was measured as follows using "Autosorb-iQ-MP" manufactured by Quantachrome Corporation. The carbon material as the measurement sample was filled into a sample tube, the sample tube was temporarily depressurized while being cooled to -196°C (77K), and then nitrogen (purity 99.999%) was adsorbed on the measurement sample at a desired relative pressure. The amount of nitrogen adsorbed on the sample when the equilibrium pressure was reached at each desired relative pressure was taken as the adsorbed gas amount v.

[0075] (Porosity measurement inside granular activated carbon)

[0076] 1. X-ray CT determination of activated carbon

[0077] The measurement was performed using Xradia 520Versa manufactured by Carl Zeiss under the following conditions.

[0078] The radiation source intensity was 120 kV, the output was 10 W, the pixel size was 1 μm, the imaging range was 1029 μm, and the exposure time was 1 s. The internal structure was displayed in a circle with a diameter of 1 mm. During the imaging, more than 1,000 images were continuously taken from the end of the granular activated carbon to the opposite end.

[0079] 2. Image processing

[0080] From the images obtained by the above-mentioned X-ray CT, more than 40 images between the first section to the last section are extracted at equal intervals. For each extracted image, Image J developed by the National Institutes of Health (NIH) of the United States is used to read and convert the image unit from pixels to the measured range (μm), and the image is converted to black and white 32Bit. The domain value of the image is set to 120, and the part judged as a hole in the X-ray CT image is blackened and displayed. The area of ​​the black range of the calculated image is divided by the measurement range to obtain the porosity of each image. The average value of the porosity obtained from the extracted image is used as the porosity of the activated carbon to be measured by X-ray CT.

[0081] (iodine adsorption)

[0082] According to JIS K 1474, activated carbon was added in varying amounts to a 0.05 mol / L iodine solution (also containing 0.15 mol / L potassium iodide). After oscillation mixing for 15 minutes, the activated carbon was separated by centrifugation, and the supernatant was titrated with 0.1 mol / L sodium thiosulfate solution to determine the residual iodine concentration. An adsorption isotherm was prepared, and the adsorption amount at a residual iodine concentration of 2.5 g / L was taken as the iodine adsorption performance.

[0083] (Average particle size of particles and activated carbon before activation)

[0084] For the particles or activated carbon before activation, a particle size cumulative curve diagram based on the mass standard is prepared based on JIS K 1474. Regarding the average particle size, in the particle size cumulative curve diagram, a horizontal line is drawn along the horizontal axis from the intersection of the vertical line of the 50% point on the horizontal axis and the particle size cumulative line, and the mesh size (mm) of the sieve shown by the intersection is obtained as the average particle size.

[0085] (Concentration of fluorinated organic compounds (PFOA, etc.) in treatment water and treated water)

[0086] The measurement was performed using a liquid chromatography-tandem mass spectrometer (LC / MS / MS) manufactured by Waters Corporation.

[0087] HPLC system body: 2695 separation module

[0088] Mobile phase solvent: 45 vol% acetonitrile / 55 vol% 0.15% acetic acid aqueous solution

[0089] ·HPLC column: Atlantis dC183μm 2.1×30mm

[0090] Tandem quadrupole mass spectrometer: Quattro microAPI

[0091] [Example 1]

[0092] As material 1, a weakly adhesive pitch carbon (adhesive index 3) having a fixed carbon content of 59.5 wt% and an ash content of 0.7 wt% was used, and as material 2, a slightly adhesive pitch carbon (adhesive index 0.5) having a fixed carbon content of 48.3 wt% or more and an ash content of 0.7 wt% and containing 45 ppm of sodium and 800 ppm of calcium was used. The above-mentioned material 1 and material 2 were mixed and pulverized in a ball mill at a weight ratio of 3:7, and the obtained powder was filled into a container with a diameter of 4 cm and a length of 15 cm using a roll press molding machine manufactured by Yamamoto Hydraulic Industry Co., Ltd., and heated at 100°C and 280 kg / cm 2 The material is press-formed under a pressure of . Then it is crushed with a jaw crusher to adjust the particle size to a particle size range of 0.1 to 2.0 mm and an average particle size of 0.95 mm.

[0093] Next, the pellets were put into an externally heated rotary kiln, heated at 5°C / min to 300°C in an oxidizing gas atmosphere, maintained at 300°C for 2 hours, and then heated at 8.75°C / min to 650°C in a reducing gas atmosphere to perform carbonization. 75.0 g of the carbonized carbon calculated based on 0 g of volatile components was charged into a fluidized furnace having an inner diameter of 57 mm and a height of 600 mm, and activated by combustion gas at 950°C with an activation yield of 50% under the flow of combustion gas of 20 L (liters, the same below) / min of air and 0.85 L / min of LPG to obtain activated carbon.

[0094] The obtained activated carbon was washed with acid water and washed with boiling water 6 times, the pH was adjusted to 6.5±0.5, and then dried at 120°C for 2 to 3 hours.

[0095] The obtained activated carbon was subjected to X-ray CT measurement under the above conditions, and the obtained graph is shown in Figure 1 The results of the image analysis are shown in Figure 2 .Depend on Figure 1 and Figure 2 It is known that the activated carbon of Example 1 has appropriate pores. In addition, various physical properties were measured according to the above-mentioned methods. The activated carbon obtained here was used to carry out the water treatment experiment described below.

[0096] [Example 2]

[0097] The pressure molding was set at 350 kg / cm 2 Activated carbon was obtained in the same manner as in Example 1 except that pressure molding was performed under 370°C. Various physical properties were measured, and the activated carbon was used to carry out the water treatment experiment described later.

[0098] [Example 3]

[0099] The pressure molding was set at 180 kg / cm 2 Activated carbon was obtained in the same manner as in Example 1 except that pressure molding was performed under 370°C. Physical properties were measured and the activated carbon was used to carry out the water treatment experiment described later.

[0100] [Example 4]

[0101] The pressure molding was set at 530 kg / cm 2 Activated carbon was obtained in the same manner as in Example 1 except that pressure molding was performed under 370°C. Physical properties were measured and the water treatment experiment described later was carried out using the activated carbon.

[0102] [Comparative Example 1]

[0103] Activated carbon was obtained in the same manner as in Example 1 except that material 2 was not mixed with material 1, but only material 1 was used, and the particle size was adjusted to a particle size range of 0.1 to 2.0 mm and an average particle size of 0.95 mm. Physical properties were measured, and the activated carbon was used to carry out the water treatment experiment described below. The obtained activated carbon was measured by X-ray CT under the above conditions, and the obtained graph is shown in FIG. Figure 3 , and the image analysis results are shown in Figure 4 . By Figure 3 and Figure 4 It can be seen that the activated carbon of Comparative Example 1 has fewer pores than that of Example 1.

[0104] [Comparative Example 2]

[0105] The pressure molding was set at 120 kg / cm 2 Activated carbon was obtained in the same manner as in Example 1 except that pressure molding was performed under 370°C. Physical properties were measured and the activated carbon was used to carry out the water treatment experiment described later.

[0106] [Comparative Example 3]

[0107] Instead of mixing material 2 with material 1, only material 1 was used, the degree of grinding was increased, and the particle size was adjusted to have particles with a particle size range of 0.01 to 0.60 mm and an average particle size of 0.08 mm. Otherwise, activated carbon was obtained in the same manner as in Example 1, and physical properties were measured. The activated carbon was also used in the water treatment experiment described later.

[0108] Table 1 shows the BET specific surface area, average particle size, porosity obtained by X-ray CT, and iodine adsorption amount of the activated carbons of Examples 1 to 4 and Comparative Examples 1 to 3.

[0109] Table 1

[0110]

[0111] (Water treatment experiment 1: penetration time determination)

[0112] Fill 10 g of the activated carbon obtained in Example 1 into a 10 mmφ×300 mm tube. Dissolve PFOA (manufactured by Aldrich, purity 96%) in tap water to a PFOA concentration of 10 ppb. Inject the solution into the activated carbon at an upflow rate of 10 ml / min to continuously obtain treated water. Continuously collect the obtained liquid, and detect the PFOA concentration in the treated water according to the above-mentioned measurement conditions. The lowest concentration among the detected PFOA concentrations is taken as the minimum PFOA detection concentration. The time when the detected PFOA concentration reaches 0.15 ppb or more is taken as the penetration time. For the activated carbons obtained in Examples 2 to 4 and Comparative Examples 1 to 3, the penetration time is also measured in the same manner as in Example 1. The results are shown in Table 2.

[0113] (Water treatment experiment 2: adsorption amount determination)

[0114] After the breakthrough time, the activated carbons obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were recovered, dried with hot air at 60°C for 12 hours, and then vacuum dried at 1 Torr and 20°C for 3 hours, and the weight increase was measured. The results are shown in Table 2.

[0115] Table 2

[0116]

[0117] (Inspection)

[0118] The results in Table 2 confirm that by using the activated carbon that meets the requirements of the embodiments of the present invention, fluorinated organic compounds (PFOA) can be removed very efficiently. On the other hand, the activated carbon in Comparative Example 1 with too small a porosity and Comparative Example 2 with too large a porosity cannot fully remove fluorinated organic compounds. In addition, in the case of Comparative Example 2 with too large a porosity, sufficient strength cannot be obtained and fragmentation occurs in a short time. In addition, the average particle size of the activated carbon in Comparative Example 3 is too small, the packing density is high, and the resistance to liquid flow becomes larger. The resistance to liquid flow increases in a shorter penetration time, and the adsorption amount of fluorinated organic compounds in the aforementioned water treatment experiment 2 is insufficient.

[0119] These results confirm that the porosity of activated carbon with a specified specific surface area and average particle size is important for the removal of fluorinated organic compounds. To a certain extent, the greater the porosity, the better the removal performance. However, when the porosity exceeds 40%, in addition to the deterioration of the removal performance, the mechanical strength also deteriorates.

[0120] This application is based on Japanese patent application No. 2020-158516 filed on September 23, 2020, and the contents are incorporated herein by reference.

[0121] In order to describe the present invention, the present invention has been appropriately and fully described in the foregoing through specific embodiments, but it should be recognized that those skilled in the art can easily change and / or improve the aforementioned embodiments. Therefore, as long as the modified embodiments or improved embodiments implemented by those skilled in the art do not deviate from the level of the protection scope of the claims recorded in the claims, the modified embodiments or improved embodiments can be interpreted as being included in the protection scope of the claims of this application.

[0122] Industrial Applicability

[0123] The activated carbon of the present invention can efficiently adsorb fluorinated organic compounds in the treatment object water. Therefore, the activated carbon of the present invention can be suitably used as a fluorinated organic compound removal material. In addition, the water treatment method of the present invention can be suitably used for the treatment and purification of factory wastewater, etc. The water treatment method of the present invention includes the above-mentioned structure, so that the treatment water with fluorinated organic compounds removed can be efficiently obtained from the treatment object water containing fluorinated organic compounds. When the concentration of fluorinated organic matter contained in the treatment object water is low, this effect of the present invention is particularly obvious.

Claims

1. A water treatment method comprising the following steps: The activated carbon is continuously brought into contact with water to be treated containing fluorine-containing organic compounds to obtain treated water having a fluorine-containing organic compound content of 0.1 ppb or less. The average particle size of the activated carbon is 0.1 to 10 mm, and the BET specific surface area is 500 m 2 / g and above and 2000m 2 / g or less, and the porosity inside the particles determined by X-ray CT is 10% or more and 40% or less.

2. The water treatment method according to claim 1, wherein: The fluorine-containing organic compound is selected from at least one of perfluoroheptanoic acid, perfluorooctanoic acid, perfluorooctanoic acid salt, perfluorononanoic acid, perfluorodecanoic acid, perfluoroundecanoic acid, perfluorododecanoic acid, perfluorooctane sulfonic acid, and perfluorooctane sulfonate.

3. The water treatment method according to claim 1, wherein: The water to be treated containing the fluorinated organic compound is passed through a column filled with the activated carbon, so that the activated carbon is brought into continuous contact with the water to be treated containing the fluorinated organic compound.

Citation Information

Patent Citations

  • Sludge-based activated carbon with effect of efficiently adsorbing PFOS (perfluorooctane sulfonate) and PFOA (perfluorooctanoic acid) and preparation method as well as application of sludge-based activated carbon

    CN106732379A

  • Activated carbon and its manufacturing method

    JP2006104002A

  • Method of adsorbing and method of recovering fluorine-containing compound

    US20100197964A1